Análise da Interiorização do Curso de Medicina da Universidade Federal do Ceará no Município de Sobral - Queiroz, Carlos Antonio de (2011)
To analyze the internalization of the medical school in the city of Sobral, based on the goals for which it was created, is the scope of this research. This is characterized as descriptive, empirical, literature, documentary and quanti-qualitative, with the universe is the graduates doctors from medical school at the Federal University of Ceará, Sobral campus, which concluded in the years 2006, 2007, 2008 and 2009. Conducted a literature search initially and documentary, which focuses the historical review of the medical courses in Brazil, the creation of the Federal University of Ceará, the origin of the medical school in the State of Ceará and its implementation in the municipality of Sobral. The field research was conducted through questionnaires and structured interviews, data were collected, tabulated and analyzed using descriptive statistics and demonstrated by means of tables, charts and graphs. From results, concluded that the objectives of this study were confirmed and thus became apparent that was right and important to the creation of the School of Medicine, Federal University of Ceará Sobral on campus. Several positive changes have occurred in the micro region Sobral are committed to fulfilling the objectives identified when designing the course and extend from the area of human resources through the opportunity to access the region's population to that course, attention, care, prevention, promotion and health care of the local population, provided by students of the course through programs and outreach projects, internship and residency. It was concluded also that the internalization of the School of Medicine, Federal University of Ceará was relevant to the municipality, and the micro region health Sobral, with the improvement in the provision of health services to the population, stimulating economic development and the region's social and especially with the establishment of the physician within the State and that this model of internalization could serve as a prototype for the MEC to spread the teaching of medicine in other regions with the same characteristics of the northern state of Ceara.